Numerical Modelling of High Efficiency Silicon Solar Cell Using Various Anti Reflective Coatings (ARC) - Jamaluddin, Nur Irdina Iwani Mohd; Yusoff, Mohd Zaki Mohd; Malek, Mohd Firdaus (Trends in Sciences, 2024)
The growing prevalence of solar in recent years, which is applied in practically every daily item comprehensively and broadly to make it simpler on consumers due to the consumption of solar resulting in a lot of savings. Anti-reflective coating (ARC) is one of the most important factors contributing to the extensive application of solar. It was acknowledged that ARC had been applied on solar cells to minimize reflection loss, enhance absorption, and boost power conversion efficiency (PCE). The efficiency of solar cell varies depending on the type of ARC material used and its specific characteristics. Since each anti-reflective coating originates from its own formula, there are many different materials produced and manufactured to be applied on solar cells. Hence, in this paper, the simulation of 6 different materials of anti-reflective coating (ARC) coatings has been analyzed and investigated using PC1D simulation software. The outcomes revealed that the ideal wavelength for developing and constructing an ARC would be around 500 and 800 nm. Silicon nitrite (Si3N4) would be the best ARC for designing a single-layer ARC due to its highest efficiency of 21.69 % and exhibits the lowest reflectance, closely followed by zinc oxide (ZnO) which has the efficiency of 21.67 %. Then, zinc sulphate (ZnS) and Titanium Oxide (TiO2) has the efficiency of 21.16 and 21.05 % respectively. While, the silicon dioxide (SiO2) has an efficiency of 20.23 % and lastly, silicon carbide (SiC) has lowest efficiency of 17.07 %. Based on the PC1D simulation software carried out in this research, the data and outcomes regarding the voltage, current, maximum power output, solar efficiency, fill factor, reflectivity, and external quantum efficiency are also reported. HIGHLIGHTS The ARC material and its properties affect solar cell efficiency This study used PC1D simulation software to evaluate 6 anti-reflective coating (ARC) materials The results showed that 500 - 800 nm is the best wavelength for ARC development and construction Silicon nitrite (Si3N4) ARC has the highest efficiency (21.69 %) and lowest reflectance, making it ideal for single-layer ARCs GRAPHICAL ABSTRACT